How skyscrapers are made - Michael, Duncan; Carpenter, Ray. (New York, NY : Facts On File Publications, 1987)
Explains how skyscrapers are built, from the preliminary designs through the floor by floor construction to the final building.
All kinds of skycrapers -- What is a skycraper? -- Planning and design -- How construction is organized -- Foundations -- Steel structures -- Concrete structures -- Cladding the exterior -- Equipping the interior -- Servicing a skyscraper -- Stage by stage -- Who creates a skyscraper? -- Great skyscrapers of the world -- The world's tallest buildings -- Glossary -- Index and acknowledgments.
Includes index.
Keywords: SKYSCRAPERS -- DESIGN AND CONSTRUCTION -- JUVENILE LITERATURE